2011
DOI: 10.1080/00223891.2011.558874
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Affect Integration: Validation of the Affect Consciousness Construct

Abstract: Affect integration, or the capacity to utilize the motivational and signal properties of affect for personal adjustment, is assumed to be an important aspect of psychological health and functioning. Affect integration has been operationalized through the affect consciousness (AC) construct as degrees of awareness, tolerance, nonverbal expression, and conceptual expression of nine discrete affects. A semistructured Affect Consciousness Interview (ACI) and separate Affect Consciousness Scales (ACSs) have been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
75
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(96 citation statements)
references
References 27 publications
21
75
0
Order By: Relevance
“…The estimates are in line with previous findings from studies of adult samples (Gude et al, 2001;Monsen et al, 1996;Monsen & Monsen, 2000;Solbakken, Hansen, Havik, & Monsen, 2011;Waller & Scheidt, 2004).…”
Section: Inter-rater Reliabilitysupporting
confidence: 91%
“…The estimates are in line with previous findings from studies of adult samples (Gude et al, 2001;Monsen et al, 1996;Monsen & Monsen, 2000;Solbakken, Hansen, Havik, & Monsen, 2011;Waller & Scheidt, 2004).…”
Section: Inter-rater Reliabilitysupporting
confidence: 91%
“…Previous studies on this topic refer mainly to interpersonal problems as assessed by IIP (Lech et al, 2008;Nicolò et al, 2011;Normann-Eide et al, 2013;Solbakken, Hansen, Havik, & Monsen, 2011). The present study extends these results by applying the outcome measure SIPP-118, which uses a different conceptualization of relational functioning, comprising central PD aspects such as capacity for intimacy, enduring relationships, and ability to feel recognition from others.…”
Section: Relational Capacitiessupporting
confidence: 55%
“…In a mixed clinical/nonclinical sample, lower levels of AC were associated with more self-reported self-image disturbances and interpersonal problems as assessed by the Structural Analysis of Social Behavior (SASB; Benjamin, 1987) and the Inventory of Interpersonal Problems-Circumplex (IIP-C; Horowitz, Rosenberg, Baer, Ureno, & Villasenor, 1988), respectively (Lech, Andersson, & Holmqvist, 2008). Correspondingly, in a previous study based on the present PD sample (Normann-Eide, Johansen, Normann-Eide, Egeland, & Wilberg, 2013), we found that low AC strongly related to poor self-esteem, measured by the Index of Self-Esteem (ISE; Hudson, 1982), as well as to interpersonal problems, as assessed by the IIP-C. An association between low AC and more severe self-related and interpersonal problems, as measured by self-report on the Minnesota Multiphasic Personality Inventory (MMPI; Havik, 1993), observer-rated quality of relationships, and the IIP, has also previously been described (Monsen, Eilertsen, Melgård, & Ødegård, 1996;Solbakken, Hansen, Havik, & Monsen, 2011).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Among the most significant findings are that affect expression is a primary channel of communication, and core affects and emotions are universal (6). It has been suggested that transactions of affect displays among humans are denser in information than any verbal communication (7). Additionally, it has been shown that facial paralysis decreases one's ability to engage in emotional contagionVthe perception and mimicking of emotions expressed by individuals in one's social environment (8,9).…”
mentioning
confidence: 97%